Phenotypic and Genotypic Characterization of Clinical Isolates Belonging to the Acinetobacter calcoaceticus-Acinetobacter baumannii (ACB) Complex Isolated From Animals Treated at a Veterinary Hospital in Switzerland - Püntener-Simmen, Sabrina; Zurfluh, Katrin; Schmitt, Sarah; Stephan, Roger; Nüesch-Inderbinen, Magdalena (Frontiers in Veterinary Science, 2019)
Objectives: We investigated a collection of strains belonging to the Acinetobacter calcoaceticus-Acinetobacter baumannii (ACB) complex obtained from a veterinary clinic with regard to their genetic relatedness, presence of antibiotic resistance genes and antimicrobial susceptibility profiles. Methods: Fifty-eight ACB-complex strains from animals treated at a veterinary clinic between 2006 and 2017, and seven strains collected from the hospital environment during 2012 were analysed. Assignment to sequence types (ST) and international complexes (IC) was done by multilocus sequence typing (MLST) according to the Pasteur scheme. Genes encoding carbapenemases, aminoglycoside-modifying enzymes, macrolide-, quinolone- and co-trimoxazole resistance genes, the ISAba1 element, virulence associated intI1 genes and plasmid associated toxin-antitoxin markers were identified by microarray. Genes encoding blaOXA-51-like carbapenemases were amplified by PCR and sequenced. Susceptibility profiles were determined by disc diffusion or by broth microdilution. Results: Among 50 A. baumannii isolates from animals, two predominant clones were observed linked to CC1 (n=27 /54% of the isolates) and CC25 (n=14/28%), respectively. Strains of IC I harbored blaOXA-69, aac(3')-la, aadA1, sul1, intI1, and splA/T genes. Isolates belonging to CC25 possessed blaOXA-64. Six (12%) isolates belonging to CC2 and carrying blaOXA-66 were also noted. One isolate belonged to CC10 (blaOXA-68), one to CC149 (blaOXA-104), the remaining isolate was assigned to ST1220 and possessed blaOXA-116. Of six environmental A. baumannii, four (66.7%) belonged to CC25 (blaOXA-64), one (16.7%) to CC2 (blaOXA-66) and one to CC3 (blaOXA-71). Nine isolates (eight from animals and one environmental strain) were non-baumannii strains and did not harbor blaOXA-51-like genes. None of the isolates carried blaOXA-23, blaOXA-48, or blaOXA-58, and none were resistant to carbapenems. Conclusions: Clonal lineages of the veterinary A. baumannii isolates in our collection are identical to those globally emerging in humans but do not harbor blaOXA-23. A. baumannii CC25 may be specific for this particular veterinary clinic environment.